Structurally Various Sorbicillinoids From an Endophytic Fungus Acremonium citrinum SS-g13 - Peng, Xiao-Ping; Li, Gang; Wang, Li-Mei; Wang, Qi; Wang, Cong; Ji, Li-Xia; Cao, Chen-Xi; Lin, Guo-Feng; Jiang, Zu-Yang; He, Zhuo-qian; Wang, Pei; Lou, Hong-Xiang (Frontiers in Microbiology, 2022)
Three new sorbicillinoids, including trimer trisorbicillinone E (1), acremosorbicillinoids A and B (2 and 3), and a new alkaloid acremokaloid A (4), and a new natural product 2S,3S-acetyl-β-methyltryptophan (5), were isolated from an endophytic fungus Acremonium citrinum SS-g13, which is found in Fructus mori plant root. In addition, eight known sorbicillinoids (6–13) were also obtained. The new compound structures were established using NMR, HRESIMS spectra, and reported spectroscopic data. The absolute configurations of compounds 1–5, were determined by spectroscopic analysis, Snatzke’s method, and time-dependent density functional theory-electronic circular dichroism (TDDFT-ECD) calculations. Compound 11 exhibited significant cholesterol efflux enhancing activity. A plausible biosynthesis pathway for the sorbicillinoids is discussed.